2021
DOI: 10.1111/acer.14669
|View full text |Cite
|
Sign up to set email alerts
|

Increased Toll‐like Receptor‐MyD88‐NFκB‐Proinflammatory neuroimmune signaling in the orbitofrontal cortex of humans with alcohol use disorder

Abstract: Background: Many brain disorders, including alcohol use disorder (AUD), are associated with induction of multiple proinflammatory genes. One aspect of proinflammatory signaling is progressive increases in expression across cells and induction of other innate immune genes. High-mobility group box 1 (HMGB1) heteromers contribute to amplification by potentiating multiple proinflammatory responses, including Tolllike receptors (TLRs). TLR signaling recruits coupling proteins linked to nuclear transcription factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 81 publications
3
30
0
Order By: Relevance
“…Expression of caspase 12 similarly positively correlates with expression of ER stress‐associated proteins and colocalizes with the NADPH oxidase NOX2. These data are consistent with concerted activation of oxidative stress and ER stress pathways within the same cell leading to cell death‐associated caspase cascades, which could contribute to the observed neuronal cell death in the OFC of individuals with AUD 1,3,7 . Indeed, in a prior study, we reported increased colocalization of the neuronal marker NeuN with the cell death marker Fluoro‐Jade B in OFC tissue samples from the same individuals used in the present investigation indicative of increased neuronal cell death in the post‐mortem human OFC of individuals with AUD 1 .…”
Section: Discussionsupporting
confidence: 91%
“…Expression of caspase 12 similarly positively correlates with expression of ER stress‐associated proteins and colocalizes with the NADPH oxidase NOX2. These data are consistent with concerted activation of oxidative stress and ER stress pathways within the same cell leading to cell death‐associated caspase cascades, which could contribute to the observed neuronal cell death in the OFC of individuals with AUD 1,3,7 . Indeed, in a prior study, we reported increased colocalization of the neuronal marker NeuN with the cell death marker Fluoro‐Jade B in OFC tissue samples from the same individuals used in the present investigation indicative of increased neuronal cell death in the post‐mortem human OFC of individuals with AUD 1 .…”
Section: Discussionsupporting
confidence: 91%
“…On a phenotypic level, there is also widespread overlap between symptoms of inflammation and of SUDs, such as anhedonia, depression, and decreased cognitive functioning [ 58 ]. In addition, in candidate gene studies in postmortem human PFC, hippocampus, and orbitofrontal cortex, increased mRNA levels of HMGB1 , which encodes a proinflammatory cytokine and toll-like receptor genes have been associated with alcohol consumption in AUD cases, providing evidence for chronic neuroinflammation in response to alcohol [ 59 61 ]. Notably, there is an overlap of findings not only on the single-gene level but also on the level of pathways and networks/modules.…”
Section: Discussionmentioning
confidence: 99%
“…While studies have found increased expression of multiple TLRs in post‐mortem human brain of AUD patients, 16 preclinical studies indicate a complex relationship with alcohol drinking. An initial experiment linking TLRs to alcohol consumption found that the TLR4 agonist and bacterial endotoxin LPS increased voluntary intake of alcohol in a two‐bottle choice model in multiple mouse strains 17 .…”
Section: Introductionmentioning
confidence: 98%